Impact of Quizizz-Based Gamification in Improving Elementary School Students' Reading Literacy - Dini Sugiarti; Iik Nurulpaik; Asep Deni Gustiana (Indonesian Journal of Education and Social Humanities, 2026)
Cultivating reading literacy in elementary education is increasingly challenging amid the distractions of the digital era, necessitating innovative, highly engaging pedagogical interventions. While digital gamification shows promise in student engagement, empirical research mapping the direct impact of platform-specific gamified assessment tools such as Quizizz on structural reading literacy outcomes remains limited. This study aims to test the effect of Quizizz-based gamification on improving elementary school students' reading literacy. Adopting a quantitative quasi-experimental design, this study involved 60 fifth-grade students, strictly assigned to an experimental class (utilizing Quizizz-based gamification) and a control class (utilizing conventional instruction). Reading literacy levels were measured via a validated assessment framework and structurally analyzed using descriptive statistics alongside paired and independent sample t-tests. The empirical results indicate that Quizizz-based gamification exerts a profoundly positive and significant effect on students' reading literacy. The experimental group demonstrated an exponential increase in mean reading literacy scores, rising from a pre-treatment baseline of 60.13 (low category) to an impressive 93.68 (very high category) post-treatment. Conversely, the control group’s post-test mean only reached 67.26 (low category), reinforcing the definitive pedagogical superiority of the gamified approach (p < 0.05). Consequently, Quizizz-based gamification serves as a highly viable pedagogical alternative to mitigate low reading literacy among elementary students. These findings offer critical insights for educators seeking to leverage game-based mechanics to transform passive reading exercises into interactive, low-stakes competitive learning environments.